2021
DOI: 10.1039/d0se01698e
|View full text |Cite
|
Sign up to set email alerts
|

The rational design of hierarchical CoS2/CuCo2S4 for three-dimensional all-solid-state hybrid supercapacitors with high energy density, rate efficiency, and operational stability

Abstract: An all-solid-state hybrid supercapacitor based on hierarchical CoS2/CuCo2S4 offers excellent rate capacitance, low charge-transfer resistance, high-rate energy density, and extended service stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
233
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(237 citation statements)
references
References 86 publications
3
233
1
Order By: Relevance
“…In addition, the peak at 717.4 eV confirmed the presence of the Fe–O bond . This result was consistent with the eigenvalue of the binding energy of Fe oxides in previous reports. , Further, the Fe 2p spectral profile exhibited two peaks at 717.4 and 733.2 eV, which were ascribed to shakeup satellites . Essentially, the XPS analysis thoroughly corroborated the existence of N and Fe elements at different states, thereby the obtained material could be identified as Fe/N co-doped porous carbon spheres.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the peak at 717.4 eV confirmed the presence of the Fe–O bond . This result was consistent with the eigenvalue of the binding energy of Fe oxides in previous reports. , Further, the Fe 2p spectral profile exhibited two peaks at 717.4 and 733.2 eV, which were ascribed to shakeup satellites . Essentially, the XPS analysis thoroughly corroborated the existence of N and Fe elements at different states, thereby the obtained material could be identified as Fe/N co-doped porous carbon spheres.…”
Section: Resultssupporting
confidence: 90%
“…This was because the larger pore volume provided more space for ion transfer, and the nitrogen-containing functional groups enhanced wettability and conductivity, both of which could reduce the ion diffusion resistance. In addition to R ct , the Nyquist plots also included a component, R s , attributed to the equivalent series resistance (ESR) [intrinsic + ionic (electrolyte) + contact (current collector|electrode interface) resistances]. , The R s values were evaluated from the intercept of the profiles touching the real axis ( Z ′). In this content, the R s values for CCPC-Fe, CCAC-Fe, CCAC-Fe-M-25%, and CCAC-Fe-M-50% were 1.87, 2.63, 2.94, and 3.29 Ω, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, to investigate the charge storage kinetics, the corresponding calibration curves for the reductive/oxidative peak currents (ip) against the square root of scan rate (ν 1/2 ) are considered, and obtained results indicated that the reaction of the charge storage on the surface of the FeCoCuS 2 electrode was a diffusion-controlled process. To confirm this, we used the equation of the power law. , …”
Section: Resultsmentioning
confidence: 99%
“…For instance, conductive core@shell NiCoSe 2 (NCSe)@Co 9 Se 8 hollow nanospheres were prepared via a two-step solvothermal route in which Co 9 Se 8 nanosheets were homogenously grown on a hollow NCSe core [181]. Similarly, various electrochemical active materials such as SnS 2 [182], CoS 2 [183], and NiMoO 4 [184], have been combined with different BMCs to build heterostructured composites.…”
Section: Fabrication Of Hierarchical Nanohybrids Of Bmcs With Metal Compoundsmentioning
confidence: 99%
“…These compound composite materials provide multiple reactive equivalents, intriguing hetero-interfaces, distinctive ion-permeable bulk microstructure, fast pathways for ion/electrolyte transfer, and appealing synergetic structural/compositional/ componental contributions, resulting in enhanced electrochemical performance. Until now, many electroactive materials including metal oxides (NiO [196], MnO 2 [230], NiMoO 4 [184], NiCoO 2 [193], Ni 3 V 2 O 8 [231], CoMoO 4 [232]), metal hydroxides (Co(OH) 2 [192,199,233], Ni(OH) 2 [188,201,202,234], Ni-Mn LDH [235,236], Ni/Co LDHs [237], FeOOH [230], Co x Ni 1−x -(OH) 2 [230], NiCo 2 (CO 3 ) 1.5 (OH) 3 [238]), metal sulfides (CoS x [239], CoS 2 [183], Co 3 S 4 [240], Co 9 S 8 [181,189,241], MoS 2 [242]), metal selenides (MoSe 2 [27,243], Ni 3 Se 2 [19]), metal phosphides (NiP [198], NiFeP [191]), and polypyrrole [244,245] have been combined with diverse BMCs as high performance electrodes for SCs. Most of these diversified heterostructured BMCs nanoarrays are grown on highly conductive substrates such as Ni-F, graphene, 3D graphene sponge, carbon paper, and CC.…”
Section: Reviewsmentioning
confidence: 99%